MEMPERBAIKI PENGUASAAN KOSAKATA SISWA DENGAN MENGGUNAKAN METODE TOTAL PHYSICAL RESPONSE DI TINGKAT KEENAM DARI SISWA SDN 001 UJUNGBATU - Elisha, Runi; Rahayu, Pipit; Sukma, Dian (Jurnal Ilmiah Mahasiswa FKIP Prodi Bahasa Inggris, 2015)
Learn vocabulary is essential to support mastery of English skills. The factors that become the obstaclesare limited number of words mastered. This research is aimed to know whether Total Physical Response (TPR)can improve studentsâ vocabulary mastery and to know the factor influence the change in the process ofstudentsâ vocabulary mastery by using TPR. The researcher conducted a classroom action research (CAR). Thedata of research were collected by using qualitative and quantitative data. There was significant improvementfrom every cycle. Cycle I: Pronunciation 60.42 (Average), spelling 66.33 (Average), meaning 66.42 (Average),grammar 66.08 (Average). Cycle II: Pronunciation 82.92 (good), spelling 82.58 (good), meaning 81.00 (good),grammar 80.00 (good)